Well-being as the main predictor of altruism over empathy among school teachers in Klang Valley, Malaysia - Muhadzir, Raudhah; Ma’rof, Aini Azeqa; Dahamat Azam, Mohamad Naqiuddin (Human Resources Management Academic Research Society (HRMARS), 2024)
In an era where the emotional and psychological well-being of educators is increasingly spotlighted, understanding the determinants of altruistic behaviors among school teachers becomes paramount. This study investigates the interplay between empathy, well-being, selfefficacy, and their collective impact on fostering altruism within educational settings. Conducted with 322 teachers from the Klang Valley, Malaysia, this research employs utilizing quantitative surveys to gauge the extent of these psychological traits and their correlation with altruistic behavior. Using the Interpersonal Reactivity Index for empathy, the Warwick Edinburgh Mental Well-being Scale for well-being, and the Teachers' Sense of Efficacy Scale for self-efficacy, alongside Pearson correlation and multiple regression analyses, the findings indicate that well-being and self-efficacy significantly predict altruistic behaviors in teachers. Although empathy alone did not directly correlate with altruism, its role in nurturing positive teacher-student relationships and a supportive classroom climate is acknowledged. This study underscores the importance of teacher well-being and self-efficacy in promoting altruism, suggesting that enhancing these aspects could lead to more empathetic and supportive educational environments. The implications of this research could guide teacher training, professional development, and educational policy towards nurturing more altruistic, compassionate educational landscapes.